مساهمة عدم الالتزام بأخلاقيات وقواعد السلوك المهني لمهنة التدقيق في انهيار شركتي انرون للطاقة وأرثر اندرسون للتدقيق - تومي, ميلود; علون, محمد لمين (Université de M'sila, 2017)
It is recently noted the increasing number of legal issues against global auditing firms, As a result of its involvement in a professional and ethical issues for several consecutive years caused the collapse of global companies such as “Enron Corporation” for energy, “WorldCom” Company, which followed by the collapse of the greatest auditing firm in the world “Arthur Andersen” as it was proved its contribution in the collapse of those companies. As a result of those huge collapses, the users of financial statements ealized the weakness of the role played by auditor in reducing the risk resulting from the issuance of inaccurate financial statements, it has emerged the need to strengthen the community's confidence in the quality of audit, it has become imperative for the auditor to prove independence and neutrality through the full applying of law , and the adherence to ethics and rules of professional conduct.
Keywords: Accounting, Auditing, Enron Corporation, Arthur Andersen for Auditing, Sarbanes–Oxley Act.